EndoBarrier Gastrointestinal Liner in Type 2 Diabetic Patients Improves Liver Fibrosis as Assessed by Liver Elastography - Gollisch, K. S. C.; Lindhorst, A.; Raddatz, D. (Experimental and Clinical Endocrinology & Diabetes, 2017)
Many obese people with type 2 diabetes develop non-alcoholic fatty liver disease, which may progress to liver fibrosis. EndoBarrier gastrointestinal liner is an innovative interventional treatment option for type 2 diabetic patients, which could affect diabetes associated liver disease. The aim of this retrospective study was to analyze the effect of 1-year EndoBarrier therapy on liver fibrosis and steatosis. As an indicator of fibrosis, liver stiffness was assessed by liver elastography at baseline, 2 weeks after EndoBarrier implantation and then every 3 months until explantation. 13/19 patients had elevated liver stiffness at baseline, corresponding to liver fibrosis grade 2 to 4. In these patients, liver stiffness reduced significantly during EndoBarrier therapy from 10.4 kPa (IQR 6.0–14.3) at baseline to 5.3 kPa (IQR 4.3–7.7, p<0.01) by the time of EndoBarrier explantation, corresponding to a normalization of the initially pathologic findings in most patients. Liver steatosis was also assessed by elastographic measurements in terms of the controlled attenuation parameter. In all patients, baseline measurements showed high grade steatosis. Improvements were seen from initially 343 dB/m (IQR 326–384) to 317 dB/m (IQR 269–375, p<0.05) by the time of explantation. However, most patients were still classified high grade steatosis after completion of EndoBarrier treatment. In this observational study, we show that liver fibrosis is a common condition in obese patients suffering from type 2 diabetes, and that EndoBarrier gastrointestinal liner substantially improves liver fibrosis in these patients.
Keywords: NAFLD; steatosis; Obesity; fibroscan; liver stiffness